The 'German View' and Consumption Booms: Empirical Evidence from Denmark - U. Michael Bergman; Michael M. Hutchison (Lund University, School of Economics and Management, Department of Economics, 1999)
We develop an alternative test of the `German view' - that a reduction in government consumption may lead to an immediate private consumption boom - derived from an open-economy permanent income model. In our empirical study we find, in accordance with the `German view', that an anticipated permanent reduction of government consumption is associated with a strong short-run (and permanent) increase in private consumption. However, the Danish experience following the fiscal contraction in 1982 suggest that this was not a dominant factor behind the private consumption boom. Our evidence shows instead that other factors increasing permanent income, including a substantial terms-of-trade improvement, were much more important.
Keywords: E21; E62; E65; 330; Expansionary fiscal contraction; German view; consumption booms; structural shocks